Algorithm for Identifying Minimum Driver Nodes Based on Structural Controllability - Reza, Haghighi; HamidReza, Namazi (Hindawi Publishing Corporation, 2015)
Existingmethods on structural controllability of networked systems are based on critical assumptions such as nodal dynamics with infinite time constants and availability of input signals to all nodes. In this paper, we relax these assumptions and examine the structural controllability for practical model of networked systems. We explore the relationship between structural controllability and graph reachability. Consequently, a simple graph-based algorithm is presented to obtain the minimum driver nodes. Finally, simulation results are presented to illustrate the performance of the proposed algorithm in dealing with large-scale networked systems.